2016
DOI: 10.19168/jyu.10880
|View full text |Cite
|
Sign up to set email alerts
|

TCMB Ağırlıklı Ortalama Fonlama Maliyeti’nin BİST100 Üzerindeki Etkisi

Abstract: The effectiveness of monetary policy instruments of the Central Banks and the impact of these tools on the market are analyzed depending on the effects of monetary policy tools on the targeted variables, and the volatility of the indicators of monetary and financial markets. According to common view, the measures which are applied or announced by central banks lead to a volatility decrease in the financial indicators. In this study, the effects of the interest rate policy of the Central Bank of the Republic of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…We briefly explain some of these studies below. Ekinci et al (2016) investigate whether the CBRT WAFC is effective on the Borsa Istanbul (BIST) 100 index and conclude that the CBRT WAFC does not affect the BIST 100 index. Küçük et al (2016) empirically analyse what determines the overnight spread between the Borsa Istanbul (BIST) repo rate and the CBRT average funding rate and find that it is recently affected by many factors both directly and closely related to the CBRT's liquidity policy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…We briefly explain some of these studies below. Ekinci et al (2016) investigate whether the CBRT WAFC is effective on the Borsa Istanbul (BIST) 100 index and conclude that the CBRT WAFC does not affect the BIST 100 index. Küçük et al (2016) empirically analyse what determines the overnight spread between the Borsa Istanbul (BIST) repo rate and the CBRT average funding rate and find that it is recently affected by many factors both directly and closely related to the CBRT's liquidity policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are many empirical studies in the literature on the CBRT WAFC. These are generally designed to investigate the relationship between the CBRT WAFC and various macroeconomic variables (e.g., Ekinci et al, 2016;Küçük et al, 2016;Tunalı & Yalçınkaya, 2017;Varlık & Berument, 2017;Güler & Özçalık, 2018;Binici et al, 2019;Büberkökü & Kızılder, 2019;Sümer, 2019;Yüksel et al, 2019;Kartal, 2020;Felek & Ceylan, 2021). Unlike these studies, we model the CBRT WAFC time series based on the monthly data for the period between 2011:01-2020:12 in the framework of autoregressive (integrated) moving average [AR(I)MA] models by using two different approaches with linear and nonlinear and investigate comparatively.…”
Section: Introductionmentioning
confidence: 99%
“…With this approach, the weighted average interest rate is calculated by taking into account the CBRT's overnight lending rate and weekly repo rate, as well as the amount of funding liquidity. This average interest rate, called the weighted average funding cost (WFC), is considered an important indicator of the monetary policy stance (Ekinci et. 2016;Kuzu, 2017).…”
Section: Datamentioning
confidence: 99%
“…On the other hand, Uyar et al (2016) find that stock indices of "XUMAL" and "XBANK" are found to be more sensitive to adverse effects from interest movements during tested period covering 2006-01-02 and 2015-01-30, suggesting investors to adjust their portfolio compositions at periods of rising or falling in the stock markets. By using daily observations, Ekinci et al (2016) discover that there are no significant effects from the weighted average cost of the CBRT funding to "XU100" over the February 21, 2013−July 26, 2016 period. Sancar et al (2017), however, find that interbank interest rate is the only factor among a set of variables including industrial production index, M1 money supply, exchange rate, consumer price index that not significantly related to stock prices in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%